Risk Management of Sugar Production Due to the Magnitude of Losses (Case Study of PT Perkebunan Nusantara X) - Ahmad Zainuddin; Intan Kartika Setyawati; Rudi Wibowo (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
High sugar consumption cannot be fulfilled by domestic sugar production. The reason is that the performance and efficiency of the national sugar mills (PG) are still relatively low. Measurement of efficiency of sugar mills can be conducted by counting the sugar losses. This study aims to (1) to analyze the value of loss index and its implications on the efficiency of sugar mills;and (2) to assess the risk due to losses. Primary and Secondary data were used in this study containing annual data of sugar mills performance indicators in PTPN X such as Overall Recovery (OR), Boiling House Recovery (BHR), Mill Extraction (ME),the amount of bagasse, the amount of filter cake, and the amount if molasses at sugar cane factory (period of 2011-2015). The data were analyzed by evaluative descriptive analysis, index calculation, and risk assessment using Failure Mode and Effect Analysis (FMEA) method. The analysis shows that the losses produced by sugar mills in Indonesia are still quite high around 2.60–2.88%. This level of losses shows the performance of sugar mills is inefficient and causes financial losses in sugar mills. Production risk assessment due to losses shows a high level of risk. Therefore, sugar mills must have a program to reduce its level of losses to the minimum level (<2%). Meanwhile, sugar mills must have programs to utilize losses to be value-added co-products.Keywords: losses, FMEA, efficiency, performance, sugar industry